Preparation method of CuCrZr wire for EMI shielding and heat dissipation net
Patent Information
- Application Number
- CN202611328360.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
传统熔炼工艺容易造成铬元素、锆元素分布不均,出现成分偏析
(1)本发明通过优化工艺顺序提高材料利用率,将传统“热锻后立即车外圆”调整为“热锻→冷轧→固溶→车外圆+多道次拉拔组合”,利用固溶后材料硬度提升、脆性增大的特点,使车削加工更加顺畅、表面质量更优,同时大幅减少材料切削损耗。
Smart Images

Figure CN122999728A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of copper alloy wire manufacturing technology, specifically to a method for preparing CuCrZr wire for EMI shielding and heat dissipation mesh. Background Technology
[0002] Avionics equipment, including airborne radar, high-power amplifiers, airborne power supplies, and engine nacelle control modules, is a core component of aircraft. During operation, this equipment generates significant electromagnetic interference and heat, while the airborne environment presents harsh conditions such as a wide temperature range (-55℃ to 250℃), high-frequency vibration, and salt spray corrosion. As a core component of the avionics equipment's ventilation system, the EMI shielding and heat dissipation mesh serves a triple function: electromagnetic shielding, ventilation and heat dissipation, and structural protection. This requires the base material to possess five key properties: high electrical conductivity, high thermal conductivity, high strength, high temperature resistance, and corrosion resistance.
[0003] Currently, the mainstream substrates for EMI shielding and heat dissipation meshes in the industry are divided into three main categories: pure copper wire, aluminum alloy wire, and stainless steel wire. Pure copper wire has the best electrical and thermal conductivity, resulting in good shielding effect, but its tensile strength is relatively low (<250MPa), it softens easily at around 200℃, and it is prone to deformation and breakage under strong vibration, leading to a shorter service life. Aluminum alloy wire has a significant advantage in lightweight design, but its electrical and thermal conductivity is average, resulting in lower shielding effectiveness, and its strength drops sharply above 150℃. Stainless steel wire has high mechanical strength and strong corrosion resistance, but its electrical and thermal conductivity is extremely poor, making it unsuitable for high-frequency electromagnetic shielding and high-power heat dissipation applications.
[0004] CuCrZr (chromium-zirconium-copper) alloy is a classic high-strength, high-conductivity copper alloy. Its high electrical and thermal conductivity, ultra-high strength, and resistance to high-temperature softening make it an ideal substrate for shielding and heat dissipation meshes used in high-temperature, high-vibration aerospace applications. Currently, mature CuCrZr wire manufacturing processes exist in China, with products mainly used in conductive terminals, conductive springs, and welding machine electrodes. However, existing processes are not specifically optimized for the needs of aerospace EMI shielding and heat dissipation meshes. Traditional smelting processes easily lead to uneven distribution of chromium and zirconium elements, resulting in compositional segregation. A single heat treatment process cannot simultaneously ensure wire strength, conductivity, and braiding performance. The lack of a dedicated protective coating on the wire surface makes it prone to oxidation in aerospace salt spray environments, leading to rapid degradation of high-frequency shielding performance. Therefore, developing a dedicated manufacturing process specifically adapted to EMI shielding and heat dissipation meshes and suited to aerospace conditions has become a pressing technical problem for the industry. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a method for preparing CuCrZr wire for EMI shielding heat dissipation mesh.
[0006] The technical solution of this invention is: a method for preparing CuCrZr wire for EMI shielding heat dissipation mesh, comprising the following steps: S1, Melting and Casting The raw materials are mixed according to the alloy composition of CuCrZr wire, and the mixed raw materials are vacuum melted and continuously cast in sequence to obtain CuCrZr alloy ingots. S2, Hot forging and cold rolling The CuCrZr alloy ingot is placed in a box-type resistance furnace and heated at a temperature of 850~950℃ for a holding time of 50~180 min to ensure uniform temperature throughout the ingot. After exiting the furnace, it is hot-forged and the final forging temperature is strictly controlled to be ≥750℃. This process can eliminate defects in the as-cast structure, refine the grains, and improve the matrix density. The hot-forged bar is then fed into a rolling mill for multiple cold rolling passes to obtain coiled wire. S3, Solution heat treatment The coiled wire is fed into a forklift-type solution furnace for solution heat treatment. The heating temperature is set to 900~990℃ and the holding time is set to 0.5~2.5 h, so that alloying elements such as chromium and zirconium can be fully dissolved into the copper matrix to form a uniform solid solution. After the holding process is completed, the wire is immediately taken out of the furnace for water quenching to quickly lock the high-temperature solid solution structure and provide conditions for subsequent aging precipitation strengthening, thus obtaining the solution-quenched wire. S4, outer circle of the car + multiple pulling stages After solution hardening, the wire is first subjected to 2-4 consecutive drawing passes, with the deformation per pass controlled at 10-25%. This improves the wire's hardness and machinability, making turning smoother and resulting in better surface quality. Compared to direct turning after hot forging, this significantly reduces material loss and improves material utilization. Then, the outer diameter is machined to thoroughly remove surface oxide scale and microcracks, ensuring uniform outer diameter and a smooth surface. The wire is then continuously drawn for 12-35 passes on the drawing machine, with the deformation per pass controlled at 10-25%, gradually drawing it to the target diameter of 0.5-1.5 mm to obtain the finished wire. During the drawing process, the wire's straightness and roundness are ensured to meet standards, with a diameter tolerance of no more than ±0.01 mm, meeting the requirements for high-precision braided mesh. By strictly controlling the wire diameter accuracy and surface quality, it adapts to the weaving requirements of 60-mesh to 100-mesh high-precision shielding and heat dissipation mesh, ensuring that the mesh's opening rate and waveguide cutoff performance meet the usage standards. S5, Aging Heat Treatment The finished wire is placed in a bell furnace for three-stage segmented aging heat treatment. After the aging is completed, the finished wire is naturally cooled to <40℃ in the furnace before being taken out of the furnace to avoid internal stress caused by rapid cooling. The method of the three-stage segmented aging heat treatment is as follows: accurately matching the precipitation sequence of multi-component alloys to balance the wire strength, conductivity and elongation. First stage (low temperature pre-aging): temperature 320~350℃, holding time 1~2 h; purpose: uniform nucleation, precipitation of a large number of diffuse and coherent GP regions to provide sufficient nucleation sites for subsequent processes. Second stage (medium-temperature transition aging): Temperature 380~420℃, holding time 1~2 h; Purpose: to promote the transformation of the GP region to the semi-coherent Cr phase, while Ni and Si elements begin to participate in the formation of composite nano-precipitates, so as to achieve uniform distribution of precipitates. Third stage (peak aging): Temperature 430~480℃, holding time 2~4 h; Purpose: to further transform the precipitated phase into stable non-coherent Cr phase and Cu5Zr phase, while fully releasing the solid solution strengthening effect of Ag, reaching the peak state of precipitation strengthening, improving matrix purity and increasing conductivity. Explanation: Synergistic effect of three-stage aging: Single-stage aging can only achieve a single precipitation stage, and two-stage aging lacks a low-temperature pre-nucleation stage, resulting in coarse precipitates. The three-stage aging of this invention achieves the following through a gradient design of "low-temperature nucleation → medium-temperature homogenization → high-temperature peak": maximizing the number density of precipitates (the first stage provides sufficient nucleation points), homogenizing the size distribution (the second stage prevents local overgrowth), and maximizing the strengthening effect (the third stage reaches the peak). All three are indispensable. S6, surface nickel plating treatment A uniform nickel plating layer with a thickness of 2-5 μm is prepared on the surface of the finished wire using a chemical nickel plating process. The nickel plating process on the wire surface has good adhesion and no defects such as pinholes or peeling. It can improve the wire's salt spray resistance and oxidation resistance, while optimizing the continuity of high-frequency electromagnetic shielding and ensuring long-term stability of high-frequency electromagnetic shielding performance. It is suitable for complex aviation environments. The finished product is then wound up to obtain CuCrZr wire for EMI shielding and heat dissipation mesh.
[0007] Furthermore, the alloy composition of the CuCrZr wire, by weight percentage, includes: chromium (Cr): 0.3%~1.2%, zirconium (Zr): 0.05%~0.25%, magnesium (Mg): 0.01%~0.05%, silicon (Si): 0.01%~0.05%, nickel (Ni): 0.01%~0.12%, silver (Ag): 0.05%~0.20%, with the balance being high-purity electrolytic copper and unavoidable impurities with a total content of ≤0.1%.
[0008] Explanation: By adopting the above-mentioned alloy composition ratio of CuCrZr wire, and by constructing a multi-component micro-alloying system, four trace elements, namely Mg, Si, Ni and Ag, are precisely added to Cu-Cr-Zr. Through the synergistic effect of multiple elements (Mg pins grain boundaries to improve creep resistance, Si forms Cr3Si high-temperature stable phase to improve heat resistance, Ni refines precipitates, and Ag improves strength while maintaining conductivity), a leapfrog improvement in comprehensive performance is achieved.
[0009] Furthermore, the vacuum melting method is as follows: a segmented electromagnetic stirring + argon refining method is adopted. Specifically, the mixed raw materials are loaded into a vacuum melting furnace, the vacuum degree inside the furnace is extracted to ≤5 Pa, and a three-stage variable frequency electromagnetic stirring is adopted; wherein, the three-stage variable frequency electromagnetic stirring method is as follows: 1) Melting period (low frequency and high current): stirring frequency 1~20 Hz, working current 200~300 A, using an intermittent start-stop method. The intermittent start-stop method is: stirring for 30~60 s and then stopping for 10~20 s, alternating in a cycle to avoid thermal stress damaging the crucible; 2) Homogenization period (medium-frequency strong magnetic field): After the mixed raw materials have initially melted, adjust the stirring frequency to 40~60 Hz, the magnetic field strength to 0.4~0.6 T, and the working current to 60~100 A, and maintain continuous stirring until the molten pool is completely liquidated and no solid particles are visually inspected. Use an infrared thermometer to detect the temperature of the molten pool and ensure that the overall temperature difference of the molten pool is ≤5℃. 3) Refining period (high frequency weak stirring + argon): Increase the electromagnetic stirring frequency to 100~130Hz, reduce the melting furnace power by 25~35 kW, slowly introduce high-purity argon into the furnace, close the argon charging valve when the furnace pressure rises to 0.05~0.1MPa, restore the melting power, and continue argon refining operation for 3~5 minutes to promote the deoxidation products to float to the surface, and at the same time remove harmful gases such as hydrogen and nitrogen from the inside of the melt.
[0010] Furthermore, the continuous casting method is as follows: after vacuum melting is completed, the power of the melting furnace is reduced by 25~35kW, the electromagnetic stirring frequency is adjusted to 20~40Hz, the melt is kept in a micro-flow state to prevent inclusion precipitation and component segregation, and the temperature is kept constant for 2 minutes; then the continuous casting operation is started, the casting speed is controlled at 5~10 kg / s, and the matching cooling water flow rate is set to 200~500 L / min to ensure uniform cooling and stable forming of the ingot; after all casting work is completed, the heating system is turned off, and the furnace is allowed to cool naturally for more than 60 minutes until the center temperature of the ingot is ≤200℃, and then the ingot is unloaded from the furnace.
[0011] Furthermore, the multi-pass cold rolling method is as follows: the total number of cold rolling passes is set to 4 to 8, the single-pass rolling deformation is controlled at 10 to 35%, the rolling speed is set to 20 to 50 m / min, and after rolling, the wire is coiled to initially reduce the wire diameter, while further refining the grains and improving the basic strength of the wire.
[0012] Furthermore, in the second stage of the three-stage segmented aging heat treatment, after holding at the temperature for 1 to 1.5 hours, a 50 Hz, 0.5 T alternating magnetic field is started and maintained for 20 to 30 minutes, and the magnetic field strength is dynamically adjusted through online resistance feedback during this period.
[0013] Explanation: By inducing micro-eddies and Lorentz forces through a 50Hz alternating field, the diffusion path of Cr / Zr atoms is disturbed, promoting three-dimensional uniform nucleation. At the same time, based on the real-time change of wire resistivity, the magnetic field strength is dynamically adjusted using a dynamic field strength adjustment formula to achieve a "precipitation state-field strength" feedback closed loop, thereby suppressing the aggregation and coarsening of precipitates caused by uneven diffusion under traditional isothermal conditions.
[0014] Furthermore, the magnetic field strength is dynamically adjusted according to the dynamic field strength regulation formula, as follows: in, B ( t The value represents the intensity of the alternating magnetic field applied in real time, expressed in tons (T). t The time points for the alternating magnetic field are expressed in minutes. B base Based on the fundamental field strength, B base =0.5 T; K p For proportional gain, the magnitude of the response error. K p =0.8 T / (μΩ·m), proportional gain, magnitude of response error; e (t) is t Point real-time error signal, in μΩ·m; K i To achieve integral gain and eliminate steady-state bias, K i =0.02 mT / (μΩ·m·s), integral gain, to eliminate steady-state bias; e ( k ) is the first k Resistivity error signal at each sampling time; The control period is set to 10 seconds. This is a nonlinear correction term used to simulate the critical threshold effect of precipitated phase nuclei; r target The target resistivity (peak aging point). r target =0.0175-0.0200 μΩ·m, target resistivity (peak aging point); r (t) is t Point real-time resistivity, in μΩ·m.
[0015] Note: The dynamic field strength regulation method exhibits significant engineering advantages over the traditional constant field strength method in the aging process of CuCrZr alloy. At the same time, the 10 s sampling period is highly coordinated with the time scale of CuCrZr precipitate dynamics, avoiding over-adjustment, oscillation or lag. Experimental results show that too fast sampling (<5s) causes noise amplification, while too slow sampling (>20s) leads to response delay. 10s is the optimal balance point.
[0016] Furthermore, the final output B(t) Saturation limiting is required, as follows: in, B final ( t (This is the final output) B ( t The amplitude is limited, with a lower limit of 0.4 T and an upper limit of 0.6 T.
[0017] Note: To ensure equipment safety and process stability, the final output must be saturated and limited. The lower limit is 0.4 T to ensure that the Lorentz force is sufficient to disturb atomic diffusion, and the upper limit is 0.6 T to avoid overheating of the copper material by eddy currents at high temperatures. This limiting mechanism is a hard physical safety boundary.
[0018] Furthermore, the resistivity change needs to be mapped to the volume fraction of precipitated phase. V p ,as follows: in, r 0 represents the resistivity of a pure Cu matrix. r 0 = 0.0172 μΩ·m; The resistance increment caused by each 1% of precipitated phase (experimental calibration value). =0.0013 μΩ·m.
[0019] The beneficial effects of this invention are: (1) This invention improves material utilization by optimizing the process sequence. The traditional "hot forging and immediately turning the outer diameter" is adjusted to "hot forging → cold rolling → solution treatment → turning the outer diameter + multi-pass drawing combination". By utilizing the characteristics of increased material hardness and increased brittleness after solution treatment, the turning process is smoother and the surface quality is better, while significantly reducing material cutting loss.
[0020] (2) This invention pioneered the "solution + three-stage aging" composite heat treatment process. Through three-stage aging (low temperature pre-aging → medium temperature transition aging → peak aging), the precipitation sequence of multi-component alloys is precisely matched, realizing the full-process control of "nucleation → transition growth → peak strengthening". This allows the wire to simultaneously possess high tensile strength (≥550MPa), high conductivity (≥80%IACS), and high elongation (≥8%), while also taking into account the vibration resistance and braiding performance. Attached Figure Description
[0021] Figure 1 This is a cross-sectional grain morphology diagram of the CuCrZr wire of this invention.
[0022] Figure 2 This is a grain morphology diagram of the longitudinal section of the CuCrZr wire of this invention. Detailed Implementation
[0023] The present invention will now be described in more detail with reference to specific embodiments, so as to better demonstrate the advantages of the present invention.
[0024] Example 1: A method for preparing CuCrZr wire for EMI shielding heat dissipation mesh, comprising the following steps: S1, Melting and Casting The raw materials are mixed according to the alloy composition of CuCrZr wire. Taking the mainstream 80-mesh aviation shielding heat dissipation mesh as an example, the alloy composition of the CuCrZr wire, by weight percentage, includes: chromium (Cr): 0.8%, zirconium (Zr): 0.15%, magnesium (Mg): 0.02%, silicon (Si): 0.03%, nickel (Ni): 0.06%, silver (Ag): 0.10%, with the balance being high-purity electrolytic copper and unavoidable impurities with a total content of ≤0.1%. The mixed raw materials are then vacuum melted and continuously cast to obtain CuCrZr alloy ingots. Vacuum melting employs a segmented electromagnetic stirring + argon refining method. Specifically, the mixed raw materials are loaded into a vacuum melting furnace, the furnace vacuum is evacuated to 4 Pa, and a three-stage variable frequency electromagnetic stirring is used. The three-stage variable frequency electromagnetic stirring method is as follows: 1) Melting period (low frequency and high current): stirring frequency 15 Hz, working current 250 A, and operation using an intermittent start-stop method. The intermittent start-stop method is: stirring for 50 s and then stopping for 15 s. 2) Homogenization period (medium-frequency strong magnetic field): After the raw materials have initially melted, adjust the stirring frequency to 50 Hz, the magnetic field strength to 0.5T, and the working current to 80 A, and maintain continuous stirring until the molten pool is completely liquidated and no solid particles are visually inspected. Use an infrared thermometer to detect the temperature of the molten pool and ensure that the overall temperature difference of the molten pool is 3℃. 3) Refining period (high frequency weak stirring + argon): Increase the electromagnetic stirring frequency to 120 Hz, reduce the melting furnace power by 30 kW, slowly introduce high-purity argon into the furnace, close the argon charging valve when the furnace pressure rises to 0.08 MPa, restore the melting power (in this example, the melting furnace power is 75 kW), and continue argon refining operation for 4 minutes to promote the deoxidation products to float to the surface, while removing harmful gases such as hydrogen and nitrogen from the inside of the melt; The continuous casting process is as follows: After vacuum melting is completed (in this example, the furnace power is 75 kW), the furnace power is reduced by 30 kW, the electromagnetic stirring frequency is adjusted to 30 Hz, the melt is kept in a micro-flow state to prevent inclusion precipitation and component segregation, and the temperature is stabilized for 2 minutes; then the continuous casting operation is started, the casting speed is controlled at 7 kg / s, and the cooling water flow rate is set to 350 L / min to ensure uniform cooling and stable forming of the ingot; after all casting work is completed, the heating system is turned off, and the furnace is allowed to cool naturally for 70 minutes until the ingot center temperature reaches 180℃, at which point the ingot is unloaded from the furnace. S2, Hot forging and cold rolling The CuCrZr alloy ingot was heated in a box-type resistance furnace at a temperature of 900℃ for 90 min to ensure uniform temperature. After being removed from the furnace, it underwent hot forging with a final forging temperature of 780℃. This process can eliminate defects in the as-cast structure, refine the grains, and improve the matrix density. The hot-forged bar was then fed into a rolling mill for multi-pass cold rolling. The total number of cold rolling passes was set to 6, with the deformation per pass controlled at 22% and the rolling speed set at 35 m / min. After rolling, the wire was coiled to initially reduce the wire diameter and further refine the grains, thereby improving the basic strength of the wire and obtaining coiled wire. S3, Solution heat treatment The coiled wire was fed into a forklift-type solution furnace for solution heat treatment. The heating temperature was set to 960℃ and the holding time was set to 1.5 h, so that alloying elements such as chromium and zirconium could be fully dissolved into the copper matrix to form a uniform solid solution. After the holding process was completed, the wire was immediately taken out of the furnace for water quenching to quickly lock the high-temperature solid solution structure and provide conditions for subsequent aging precipitation strengthening, thus obtaining the solution-quenched wire. S4, outer circle of the car + multiple pulling stages After solution hardening, the wire undergoes three consecutive drawing passes with a single-pass deformation of 18%, improving its hardness and machinability, making turning smoother and resulting in better surface quality. Compared to direct turning after hot forging, this significantly reduces material loss and improves material utilization. The outer diameter is then machined to thoroughly remove surface oxide scale and microcracks, ensuring uniform outer diameter and a smooth surface. After outer diameter machining, the wire undergoes another 25 consecutive drawing passes on a drawing machine, with the single-pass deformation controlled at 18%, gradually drawing the wire to the target diameter of 1.0 mm to obtain the finished wire. The drawing process ensures the wire's straightness and roundness meet standards, with a diameter tolerance of ±0.008 mm, satisfying the requirements for high-precision braided mesh. By strictly controlling the wire diameter accuracy and surface quality, it adapts to the weaving requirements of 80-mesh high-precision shielding and heat dissipation mesh, ensuring that the mesh's aperture ratio and waveguide cutoff performance meet the usage standards.
[0025] S5, Aging Heat Treatment The finished wire is placed in a bell furnace for three-stage segmented aging heat treatment. After the aging is completed, the finished wire is naturally cooled to <40℃ in the furnace before being taken out of the furnace to avoid internal stress caused by rapid cooling. The method of the three-stage segmented aging heat treatment is as follows: accurately matching the precipitation sequence of multi-component alloys to balance the wire strength, conductivity and elongation. First stage (low temperature pre-aging): temperature 330℃, holding time 1.5 h; purpose: uniform nucleation, precipitation of a large number of diffuse and coherent GP regions, providing sufficient nucleation sites for subsequent processes.
[0026] Second stage (intermediate temperature transition aging): temperature 400℃, holding time 1.5 h; purpose: to promote the transformation of the GP region to the semi-coherent Cr phase, while Ni and Si elements begin to participate in the formation of composite nano-precipitates, so as to achieve uniform distribution of precipitates.
[0027] Level 3 (Peak Aging): Temperature 460℃, holding time 3 h; Purpose: to further transform the precipitated phase into stable incoherent Cr phase and Cu5Zr phase, while fully releasing the solid solution strengthening effect of Ag, reaching the peak state of precipitation strengthening, improving matrix purity and increasing conductivity. S6, surface nickel plating treatment A uniform nickel plating layer with a thickness of 3 μm is prepared on the surface of the finished wire using a chemical nickel plating process. The nickel plating process on the wire surface has good adhesion and no defects such as pinholes or peeling. It can improve the wire's salt spray resistance and oxidation resistance, while optimizing the continuity of high-frequency electromagnetic shielding and ensuring long-term stability of high-frequency electromagnetic shielding performance. It is suitable for complex aviation environments. The finished product is then wound up to obtain CuCrZr wire for EMI shielding and heat dissipation mesh.
[0028] The electroless nickel plating process involves the following steps: The finished wire is sequentially subjected to three stages of alkaline degreasing (NaOH 60 g / L, 70℃, 8 min), acid pickling and activation (12% sulfuric acid solution, room temperature, 45 s), and deionized water rinsing. The pH of the plating solution is adjusted to 5.0 using ammonia or glacial acetic acid. The plating temperature is controlled at 88±3℃. The plating time is adjusted according to the required plating thickness (deposition rate approximately 1500~1550 μm / h, plating thickness 3 μm corresponds to approximately 10~12 min). During plating, gentle mechanical stirring or slow reciprocating motion of the wire is used to ensure plating uniformity. It should be noted that the above electroless nickel plating process is for illustrative purposes only and does not impose any specific limitations. Different electroless nickel plating methods or nickel plating processes can be adopted according to production and manufacturing requirements.
[0029] Example 2: The difference between this example and Example 1 is that the alloy composition of the CuCrZr wire includes: chromium (Cr): 0.3%, zirconium (Zr): 0.05%, magnesium (Mg): 0.01%, silicon (Si): 0.01%, nickel (Ni): 0.01%, silver (Ag): 0.05%, with the balance being high-purity electrolytic copper and unavoidable impurities with a total content of ≤0.1%.
[0030] Example 3: The difference between this example and Example 1 is that the alloy composition of the CuCrZr wire includes: chromium (Cr): 1.2%, zirconium (Zr): 0.25%, magnesium (Mg): 0.05%, silicon (Si): 0.05%, nickel (Ni): 0.12%, silver (Ag): 0.20%, and the balance is high-purity electrolytic copper and unavoidable impurities with a total content of ≤0.1%.
[0031] Example 4: This example differs from Example 1 in that the three-stage variable frequency electromagnetic stirring method is as follows: 1) Melting period (low frequency and high current): stirring frequency 1Hz, working current 200A, and operation using an intermittent start-stop method. The intermittent start-stop method is: stirring for 30 seconds and then stopping for 10 seconds. 2) Homogenization period (medium frequency strong magnetic field): After the raw materials have initially melted, adjust the stirring frequency to 40 Hz, the magnetic field strength to 0.4T, and the working current to 60 A, and keep stirring continuously until the molten pool is completely liquid. Use an infrared thermometer to detect the temperature of the molten pool and ensure that the overall temperature difference of the molten pool is 2℃. 3) Refining period (high frequency weak stirring + argon): Increase the electromagnetic stirring frequency to 100 Hz, reduce the melting furnace power by 25 kW, slowly introduce high-purity argon into the furnace, close the argon charging valve when the furnace pressure rises to 0.05 MPa, restore the melting power, and continue argon refining operation for 3 minutes.
[0032] Example 5: This example differs from Example 1 in that the three-stage variable frequency electromagnetic stirring method is as follows: 1) Melting period (low frequency and high current): stirring frequency 20Hz, working current 300A, and operation using an intermittent start-stop method. The intermittent start-stop method is: stirring for 60 seconds and then stopping for 20 seconds. 2) Homogenization period (medium frequency strong magnetic field): After the raw materials have initially melted, adjust the stirring frequency to 60 Hz, the magnetic field strength to 0.6T, and the working current to 100 A, and keep stirring continuously until the molten pool is completely liquid. Use an infrared thermometer to detect the temperature of the molten pool and ensure that the overall temperature difference of the molten pool is 5℃. 3) Refining period (high frequency weak stirring + argon): Increase the electromagnetic stirring frequency to 130 Hz, reduce the melting furnace power by 35 kW, slowly introduce high-purity argon into the furnace, close the argon charging valve when the furnace pressure rises to 0.1 MPa, restore the melting power, and continue argon refining operation for 5 minutes.
[0033] Example 6: The difference between this example and Example 1 is that the continuous casting is as follows: After vacuum melting is completed, the power of the melting furnace is reduced by 25 kW, the electromagnetic stirring frequency is adjusted to 20 Hz, and the temperature is kept constant for 2 minutes; then the continuous casting operation is started, the casting speed is controlled at 5 kg / s, and the cooling water flow rate is set to 200 L / min; after all casting work is completed, the heating system is turned off, and the furnace is allowed to cool naturally for 65 minutes until the center temperature of the ingot reaches 160℃, and then the ingot is unloaded from the furnace.
[0034] Example 7: The difference between this example and Example 1 is that the continuous casting is as follows: After vacuum melting is completed, the power of the melting furnace is reduced by 35 kW, the electromagnetic stirring frequency is adjusted to 40 Hz, and the temperature is kept constant for 2 minutes; then the continuous casting operation is started, the casting speed is controlled at 10 kg / s, and the cooling water flow rate is set to 500 L / min; after all the casting work is completed, the heating system is turned off, and the furnace is allowed to cool naturally for 80 minutes until the center temperature of the ingot reaches 200℃, and then the ingot is unloaded from the furnace.
[0035] Example 8: The difference between this example and Example 1 is that the CuCrZr alloy ingot is placed in a box-type resistance furnace and heated at a temperature of 850°C for 50 minutes. After being taken out of the furnace, it is hot forged, and the final forging temperature is strictly controlled at 750°C.
[0036] Example 9: The difference between this example and Example 1 is that the CuCrZr alloy ingot is placed in a box-type resistance furnace for heating. The heating temperature is set to 950℃ and the holding time is set to 180 min. After being taken out of the furnace, it is hot forged, and the final forging temperature is strictly controlled at 800℃.
[0037] Example 10: The difference between this example and Example 1 is that the hot-forged bar is fed into a rolling mill for multi-pass cold rolling. The total number of cold rolling passes is set to 4, the deformation per pass is controlled at 10%, the rolling speed is set to 20 m / min, and the wire is coiled after rolling to obtain coiled wire.
[0038] Example 11: The difference between this example and Example 1 is that the hot-forged bar is fed into a rolling mill for multi-pass cold rolling. The total number of cold rolling passes is set to 8, the deformation per pass is controlled at 35%, the rolling speed is set to 50 m / min, and the wire is coiled after rolling to obtain coiled wire.
[0039] Example 12: The difference between this example and Example 1 is that the coiled wire is fed into a forklift-type solution furnace for solution heat treatment, the heating temperature is set to 900℃, and the holding time is set to 0.5 h.
[0040] Example 13: The difference between this example and Example 1 is that the coiled wire is fed into a forklift-type solution furnace for solution heat treatment, the heating temperature is set to 990℃, and the holding time is set to 2.5 h.
[0041] Example 14: The difference between this example and Example 1 is that two consecutive drawing passes are performed first, with a single drawing deformation of 10%; then, 12 consecutive drawing passes are performed on the drawing machine, with the single drawing deformation controlled at 10%, gradually drawing the wire to the target wire diameter of 0.5 mm to obtain the finished wire size.
[0042] Example 15: The difference between this example and Example 1 is that four consecutive drawing passes are performed first, with a single-pass drawing deformation of 25%; then, 35 consecutive drawing passes are performed on the drawing machine, with the single-pass drawing deformation controlled at 25%, gradually drawing the wire to the target wire diameter of 1.5mm to obtain the finished wire size.
[0043] Example 16: The difference between this example and Example 1 is that the three-stage segmented aging heat treatment method is as follows: First stage (low temperature pre-aging): temperature 320℃, holding time 1 h; Second stage (medium temperature transition aging): temperature 380℃, holding time 1 h; Third stage (peak aging): temperature 430℃, holding time 2 h.
[0044] Example 17: The difference between this example and Example 1 is that the three-stage segmented aging heat treatment method is as follows: First stage (low temperature pre-aging): temperature 350℃, holding time 2 h; Second stage (medium temperature transition aging): temperature 420℃, holding time 2 h; Third stage (peak aging): temperature 480℃, holding time 4 h.
[0045] Example 18: This example differs from Example 1 in that a uniform nickel plating layer with a thickness of 2 μm is prepared on the surface of the wire.
[0046] Example 19: This example differs from Example 1 in that a uniform nickel plating layer with a thickness of 5 μm is prepared on the surface of the wire.
[0047] Example 20: This example differs from Example 1 in that, in the second stage of the three-stage segmented aging heat treatment, after holding for 1 hour, a 50 Hz, 0.5 T alternating magnetic field is activated and maintained for 30 minutes. During this period, the magnetic field strength is dynamically adjusted via online resistance feedback. The dynamically adjusted magnetic field strength is adjusted according to the dynamic field strength adjustment formula, as follows: (1) (2) (3) in, B ( t The value represents the intensity of the alternating magnetic field applied in real time, expressed in tons (T). t The time points for the alternating magnetic field are expressed in minutes. B base Based on the fundamental field strength, B base =0.5 T; K p For proportional gain, the magnitude of the response error. K p =0.8 T / (μΩ·m); e ( t )for t Point real-time error signal, in μΩ·m; K i To achieve integral gain and eliminate steady-state bias, K i =0.02 mT / (μΩ·m·s); e ( k ) is the first k Resistivity error signal at each sampling time; The control period is set to 10 seconds. This is a nonlinear correction term used to simulate the critical threshold effect of precipitated phase nuclei; r target The target resistivity (peak aging point). r target =0.0175-0.0200 μΩ·m; r (t) is tPoint real-time resistivity, in μΩ·m.
[0048] Among these, the resistivity change needs to be mapped to the volume fraction of precipitated phase. V p ,as follows: in, r 0 represents the resistivity of a pure Cu matrix. r 0 = 0.0172 μΩ·m; The resistance increment caused by each 1% of precipitated phase (experimental calibration value). =0.0013 μΩ·m.
[0049] r target The values are selected based on the resistivity of the CuCrZr alloy at the peak aging point, and are generally distributed in the range of 0.0175-0.0220 μΩ·m. The following are some examples for illustration: 0.0175 μΩ·m: Typically suitable for applications prioritizing high conductivity; 0.0185 μΩ·m: This is typically applicable to the optimal operating condition for strong conduction balance. 0.0220 μΩ·m: Typically used for high-strength structural components; In this embodiment, the value is 0.0185 μΩ·m.
[0050] Taking t=90 min as an example, r target =0.0185 μΩ·m, measured r ( t Substituting 0.0178 μΩ·m into equation (2), we get: e ( t ) = 0.0185 - 0.0178 = +0.0007, then... e ( t Substituting the value into equation (3), we get: =+0.1·(0.7) 2 =+0.049 T PID item ( ): 0.8×0.0007+0.02×sum≈+0.00056 T Total field strength B(t) : B(t) =0.5 + 0.00056 + 0.049 = 0.5496 T At the same time, the final output B(t) Saturation limiting is required, as follows: in, B final ( t (This is the final output) B ( t The amplitude is limited, with a lower limit of 0.4 T and an upper limit of 0.6 T.
[0051] After bandwidth limiting: B final ( t If t = 0.55 T, then at t = 90 min, the system automatically increases the field strength to 0.55 T, enhancing atomic perturbation and accelerating nucleation.
[0052] Among them, the average error within 1.5h (5400s) is =+0.00005 μΩ·m, then: sum≈540×0.00005×10=0.27 μΩ·m·s Corresponding integral output: =0.02×sum=0.02×0.27=0.0054 mT.
[0053] It should be noted that the above-mentioned control process can be achieved using a four-probe method (such as KDA-1 or LBRRT-1000), which provides: constant current source accuracy of ±0.05%, voltage resolution of 10 μV, and resistivity measurement resolution up to 1×10⁻⁶. -5 Ω·cm=0.00001 μΩ·m; at the same time, the system integrates real-time temperature sensing (±0.1 ℃), automatically corrects the temperature coefficient of resistivity (CuCrZr≈0.4 % / ℃), and can be set with differential measurement structure + shielded electrode to suppress electromagnetic interference and contact resistance drift.
[0054] Example 21: The difference between this example and Example 20 is that, after heat preservation for 1 h, a 50 Hz, 0.5 T alternating magnetic field is started and maintained for 25 min.
[0055] Example 22: The difference between this example and Example 20 is that, after heat preservation for 1 h, a 50 Hz, 0.5 T alternating magnetic field is started and maintained for 20 min.
[0056] Experimental example: The performance of CuCrZr wire was tested using mainstream 80-mesh aerospace shielding and heat dissipation mesh. Multiple performance tests were conducted on the CuCrZr wire prepared in Example 1 (average results were taken), and the results are as follows: Tensile strength 592MPa, electrical conductivity 83% IACS, thermal conductivity 342W / (m·K), softening temperature 585℃, elongation 9.5%.
[0057] CuCrZr wire was woven into an 80-mesh shielding mesh with an 80% open area ratio, achieving a shielding effectiveness of 82dB in the 200MHz to 10GHz frequency band. No corrosion was observed after 500 hours of salt spray testing, and no deformation or wire breakage was observed after 5000 hours of high-temperature vibration testing at 250℃.
[0058] It can be seen that the CuCrZr wire prepared by the method of the present invention has high tensile strength (≥550MPa), high conductivity (≥80%IACS), and high elongation (≥8%), while taking into account both vibration resistance and braiding performance.
[0059] Meanwhile, in order to verify the core process steps of the preparation method of this invention, the following investigation is conducted: (1) To verify the effect of the three-stage aging process on the performance of the prepared CuCrZr wire, the following comparative examples were set up: Comparative Example 1 (traditional single-stage aging, without the addition of multi-component microalloying elements): a traditional CuCrZr ternary alloy (Cr 0.8%, Zr 0.15%, without the addition of Mg, Si, Ni, and Ag) was used, followed by single-stage aging (450℃×4h) after solution treatment. The remaining processes were the same as in Example 1.
[0060] Finished product properties: tensile strength 465MPa, electrical conductivity 74% IACS, thermal conductivity 295W / (m·K), softening temperature 510℃, elongation 5.5%. The breakage rate is as high as 38% when weaving an 80-mesh net, making continuous weaving impossible.
[0061] Comparative Example 2 (with added multi-component microalloying elements, but using two-stage aging): The same multi-component alloy composition as in Example 1 (Cr 0.8%, Zr 0.15%, Mg 0.02%, Si 0.03%, Ni 0.06%, Ag 0.10%) was used. After solution treatment, two-stage aging was performed (low temperature 350℃×2h→high temperature 460℃×3h). The remaining processes were the same as in Example 1.
[0062] Finished product properties: tensile strength 525MPa, electrical conductivity 78% IACS, thermal conductivity 315W / (m·K), softening temperature 545℃, elongation 7.2%. The breakage rate is approximately 12% when weaving an 80-mesh net.
[0063] Comparative Example 3 (using three-stage aging, but without the addition of multi-component microalloying elements): a traditional CuCrZr ternary alloy (Cr 0.8%, Zr 0.15%, no Mg, Si, Ni, Ag added) was used, and the same three-stage aging process as in Example 1 was employed.
[0064] Finished product properties: tensile strength 505 MPa, electrical conductivity 76% IACS, thermal conductivity 305 W / (m·K), softening temperature 530℃, elongation 6.8%. The breakage rate is approximately 18% when weaving an 80-mesh net.
[0065] The overall performance comparison of Comparative Examples 1, 2, and 3 is shown in Table 1 below:
[0066] Compared to Comparative Example 1, Example 1 showed a 27.3% increase in tensile strength, a 12.2% increase in conductivity, a 75°C increase in softening temperature, a 72.7% increase in elongation, and a reduction in braid breakage rate from 38% to below 2%. For Comparative Example 2, Example 1 showed a 12.8% increase in tensile strength, a 6.4% increase in conductivity, a 40°C increase in softening temperature, and a 31.9% increase in elongation, demonstrating that three-stage aging has a significant performance advantage over two-stage aging. Compared to Comparative Example 3, Example 1 showed a 17.2% increase in tensile strength, a 9.2% increase in conductivity, a 55°C increase in softening temperature, and a 39.7% increase in elongation. This confirms a significant synergistic enhancement effect between multi-component microalloying and three-stage aging—the combination of "multi-component addition" and "three-stage aging" produces a synergistic effect of "1+1>2", rather than a simple superposition of their individual effects. It can be seen that by precisely matching the precipitation sequence of multi-component alloys through the three-stage aging (low temperature pre-aging → medium temperature transition aging → peak aging) of this invention, the entire process of "nucleation → transition growth → peak enhancement" can be controlled, allowing the wire to simultaneously possess high tensile strength, high conductivity, and high elongation.
[0067] (2) To verify the effect of different three-stage aging processes on the performance of the prepared CuCrZr wire, the CuCrZr wire prepared in Example 20 was subjected to multiple finished product performance tests (average value was taken), and the results are as follows: Tensile strength 627MPa, electrical conductivity 82% IACS, thermal conductivity 338W / (m·K), softening temperature 580℃, elongation 10.3%.
[0068] CuCrZr wire was woven into an 80-mesh shielding mesh with an 80% open area ratio, achieving a shielding effectiveness of 82dB in the 200MHz to 10GHz frequency band. No corrosion was observed after 500 hours of salt spray testing, and no deformation or wire breakage was observed after 5000 hours of high-temperature vibration testing at 250℃.
[0069] Comparative Example 4 was set up (using magnetic field-assisted second stage, but using a constant magnetic field): In the second stage of the three-stage segmented aging heat treatment, after holding for 1 h, a 50 Hz, 0.5 T magnetic field was started and maintained for 30 min, and the rest of the process was the same as in Example 1.
[0070] The overall performance comparison between Example 20 and Example 1 is shown in Table 2 below:
[0071] Compared to Example 1, Example 20 has better overall performance, with a significant reduction in the breakage rate of its 80-mesh braid. This shows that by dynamically adjusting the magnetic field strength using a dynamic field strength adjustment formula based on the real-time change of wire resistivity, a feedback loop of "precipitation state-field strength" can be achieved to suppress the aggregation and coarsening of precipitated phases caused by uneven diffusion under traditional constant temperature conditions. This results in CuCrZr wires with superior performance for use in EMI shielding heat dissipation meshes.
[0072] Meanwhile, observation of the cross-sectional morphology of the prepared CuCrZr wire revealed that, for example... Figure 1 , Figure 2 As shown, its structure is dense and its texture is uniform, indicating that CuCrZr material is of excellent quality.
Claims
1. A method for preparing CuCrZr wire for EMI shielding heat dissipation mesh, characterized in that, Includes the following steps: S1. Melting and casting: The raw materials are mixed according to the alloy composition of CuCrZr wire, and the mixed raw materials are vacuum melted and continuously cast in sequence to obtain CuCrZr alloy ingots. S2. Hot forging and cold rolling: The CuCrZr alloy ingot is placed in a box-type resistance furnace and heated to a temperature of 850~950℃ for 50~180 min. After exiting the furnace, it is hot forged and the final forging temperature is strictly controlled to be ≥750℃. Then, the hot forged bar is sent to a rolling mill for multiple cold rolling passes to obtain coiled wire. S3. Solution heat treatment: The coiled wire is sent into a forklift-type solution furnace for solution heat treatment. The heating temperature is 900~990℃ and the holding time is 0.5~2.5 h. Then it is immediately taken out of the furnace and water quenched to obtain the solution-quenched wire. S4. Turning the outer diameter + multi-pass drawing: After solution quenching, the wire is first drawn continuously for 2 to 4 passes, with a single pass drawing deformation of 10 to 25%. Then, the outer diameter is turned. After that, it is drawn continuously for 12 to 35 passes on the drawing machine, with the single pass drawing deformation controlled at 10 to 25%. The wire is gradually drawn to the target wire diameter of 0.5 to 1.5 mm to obtain the finished wire size. S5. Aging heat treatment: The finished wire is placed in a bell furnace for three-stage segmented aging heat treatment. The finished wire is cooled to <40℃ in the furnace before being taken out. The three-stage segmented aging heat treatment method is as follows: First stage: temperature 320~350℃, holding time 1~2 h; Second stage: temperature 380~420℃, holding time 1~2 h. Level 3: Temperature 430~480℃, heat preservation time 2~4 hours; S6. Surface nickel plating treatment: A uniform nickel plating layer with a thickness of 2~5 μm is prepared on the surface of the finished wire, and then the finished product is wound up to obtain CuCrZr wire for EMI shielding heat dissipation mesh.
2. The method for preparing CuCrZr wire for EMI shielding heat dissipation mesh according to claim 1, characterized in that, The alloy composition of the CuCrZr wire, by weight percentage, includes: chromium: 0.3%~1.2%, zirconium: 0.05%~0.25%, magnesium: 0.01%~0.05%, silicon: 0.01%~0.05%, nickel: 0.01%~0.12%, silver: 0.05%~0.20%, with the balance being copper.
3. The method for preparing CuCrZr wire for EMI shielding heat dissipation mesh according to claim 1, characterized in that, The vacuum melting method is as follows: raw materials are mixed according to the alloy composition of CuCrZr wire, the mixed raw materials are loaded into a vacuum melting furnace, the vacuum level inside the furnace is reduced to ≤5Pa, and a three-stage variable frequency electromagnetic stirring is employed; wherein, the three-stage variable frequency electromagnetic stirring method is as follows: 1) Melting period: Stirring frequency 1~20 Hz, working current 200~300 A, using an intermittent start-stop method, wherein the intermittent start-stop method is: stirring for 30~60 s and then stopping for 10~20 s; 2) Homogenization period: After the mixed raw materials have initially melted, adjust the stirring frequency to 40~60 Hz, the magnetic field strength to 0.4~0.6 T, and the working current to 60~100 A, and keep stirring continuously until the molten pool is completely liquidized; 3) Refining period: Increase the electromagnetic stirring frequency to 100~130 Hz, reduce the melting furnace power by 25~35 kW, slowly introduce high-purity argon into the furnace, and close the argon charging valve when the furnace pressure rises to 0.05~0.1 MPa, restore the melting power, and continue for 3~5 minutes.
4. The method for preparing CuCrZr wire for EMI shielding heat dissipation mesh according to claim 3, characterized in that, The continuous casting method is as follows: after vacuum melting is completed, the power of the melting furnace is reduced by 25~35 kW, the electromagnetic stirring frequency is adjusted to 20~40 Hz, and the temperature is kept constant for 2 minutes; then the continuous casting operation is started, the casting speed is 5~10 kg / s, and the cooling water flow rate is 200~500 L / min; after all casting work is completed, the heating system is turned off, and the furnace is allowed to cool naturally until the center temperature of the ingot is ≤200℃, and then the ingot is unloaded from the furnace.
5. The method for preparing CuCrZr wire for EMI shielding heat dissipation mesh according to claim 1, characterized in that, The multi-pass cold rolling method is as follows: the total number of cold rolling passes is 4 to 8, the deformation per pass is 10 to 35%, the rolling speed is 20 to 50 m / min, and the wire is coiled after rolling.
6. The method for preparing CuCrZr wire for EMI shielding heat dissipation mesh according to claim 1, characterized in that, In the second stage of the three-stage segmented aging heat treatment, after holding for 1 to 1.5 hours, a 50 Hz, 0.5 T alternating magnetic field is started and maintained for 20 to 30 minutes, and the magnetic field strength is dynamically adjusted through online resistance feedback during this period.
7. The method for preparing CuCrZr wire for EMI shielding heat dissipation mesh according to claim 6, characterized in that, The magnetic field strength is dynamically adjusted according to the dynamic field strength regulation formula, as follows: in, B ( t The value represents the intensity of the alternating magnetic field applied in real time, expressed in tons (T). t The time points for the alternating magnetic field are expressed in minutes. B base Based on the fundamental field strength, B base =0.5 T; K p For proportional gain, K p =0.8 T / (μΩ·m); e (t) is t Point real-time error signal, in μΩ·m; K i For integral gain, K i =0.02 mT / (μΩ·m·s); e ( k ) is the first k Resistivity error signal at each sampling time; The control period is set to 10 seconds. This is a nonlinear correction term; ρ target For the target resistivity, ρ target =0.0175-0.0200 μΩ·m; ρ (t) is t Point real-time resistivity, in μΩ·m.
8. The method for preparing CuCrZr wire for EMI shielding heat dissipation mesh according to claim 7, characterized in that, Final output B(t) Saturation limiting is required, as follows: in, B final ( t (This is the final output) B ( t The amplitude is limited, with a lower limit of 0.4 T and an upper limit of 0.6 T.
9. The method for preparing CuCrZr wire for EMI shielding heat dissipation mesh according to claim 7, characterized in that, The resistivity change needs to be mapped to the volume fraction of precipitated phase. V p ,as follows: in, ρ 0 represents the resistivity of a pure Cu matrix. ρ 0 = 0.0172 μΩ·m; The increase in resistance caused by each 1% of precipitated phase. =0.0013 μΩ·m.
